2021
DOI: 10.3390/medicina57020143
|View full text |Cite
|
Sign up to set email alerts
|

Made in Germany: A Quality Indicator Not Only in the Automobile Industry But Also When It Comes to Skin Replacement: How an Automobile Textile Research Institute Developed a New Skin Substitute

Abstract: Successful research and development cooperation between a textile research institute, the German Federal Ministry of Education and Research via the Center for Biomaterials and Organ Substitutes, the University of Tübingen, and the Burn Center of Marienhospital, Stuttgart, Germany, led to the development of a fully synthetic resorbable temporary epidermal skin substitute for the treatment of burns, burn-like syndromes, donor areas, and chronic wounds. This article describes the demands of the product and the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 105 publications
(148 reference statements)
0
5
0
Order By: Relevance
“…21 In accordance with the presented findings, previous studies have demonstrated a reduction of bleeding following polylactic acid membrane defect coverage. 11,22 However, epithelialization was achieved comparably between groups. According to the literature, epithelialization of donor sites requires 7 to 21 days.…”
Section: Discussionmentioning
confidence: 92%
“…21 In accordance with the presented findings, previous studies have demonstrated a reduction of bleeding following polylactic acid membrane defect coverage. 11,22 However, epithelialization was achieved comparably between groups. According to the literature, epithelialization of donor sites requires 7 to 21 days.…”
Section: Discussionmentioning
confidence: 92%
“…The polylactide wound dressing Suprathel was initially designed to treat burn wounds. 7 Consequently, several studies have investigated its effectiveness on burn wounds of different degrees with promising results. 17 , 18 Its use as an epidermal skin substitute with no need for frequent dressing changes makes it an effective wound dressing for split‐thickness skin donor sites.…”
Section: Discussionmentioning
confidence: 99%
“… 22 , 24 With advanced wound healing, a wound's pH decreases towards more acidic, and the typical pH values of the surface of healed skin of 4 to 6. 13 , 25 , 26 , 27 This release of lactate anions, which is the working principle of Suprathel, 7 might cause a marked reduction of bacterial load. 28 Furthermore, the postulated increase of lactate as energy provider for wound healing and inductor of cytokines ultimately catalyses the resumption of the wound healing cascade.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations